2019
DOI: 10.1097/spv.0000000000000740
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Ketorolac With Ibuprofen for Postoperative Pain: A Randomized Clinical Trial

Abstract: Objectives The objective of this study was to identify differences in pain perception and satisfaction with pain control in women receiving nonsteroidal anti-inflammatory drugs postoperatively. Methods This was a prospective, randomized controlled trial including urogynecology surgical patients. After surgery, all patients were randomized to receive either intravenous (IV) ketorolac or ibuprofen. The patients completed 3 visual analog scales (VAS) asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 14 publications
2
15
0
1
Order By: Relevance
“…Ketorolac is often used in patients who cannot tolerate oral medications. In a randomized trial to assess the benefit of ketorolac (vs. placebo) after outpatient urogynecological surgery, a single IV dose did not reduce pain or opioid use 69 . In a larger study comparing IV ibuprofen to IV ketorolac in FPMRS patients, there was no difference in pain, satisfaction, or opioid use postoperatively 70 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketorolac is often used in patients who cannot tolerate oral medications. In a randomized trial to assess the benefit of ketorolac (vs. placebo) after outpatient urogynecological surgery, a single IV dose did not reduce pain or opioid use 69 . In a larger study comparing IV ibuprofen to IV ketorolac in FPMRS patients, there was no difference in pain, satisfaction, or opioid use postoperatively 70 …”
Section: Resultsmentioning
confidence: 99%
“…In a randomized trial to assess the benefit of ketorolac (vs. placebo) after outpatient urogynecological surgery, a single IV dose did not reduce pain or opioid use. 69 In a larger study comparing IV ibuprofen to IV ketorolac in FPMRS patients, there was no difference in pain, satisfaction, or opioid use postoperatively. 70 (2) Gabapentinoids While gabapentinoids (gabapentin and pregabalin) have been part of ERAS protocols, recent evidence questions their effectiveness in reducing postoperative opioid requirements.…”
Section: Multimodal Medicationsmentioning
confidence: 91%
“…Earlier studies with oral ibuprofen (200–600 mg) demonstrated improved migraine pain relief versus placebo at 2 h 20–23 . IV ibuprofen (800 mg in 250 ml saline) has been studied for adjunctive postoperative pain management 24,25 ; in these trials, the efficacy of IV ibuprofen appears comparable with that of IV ketorolac on pain reduction (visual analog scale; VAS) 17,26 . For use in migraine, IV ibuprofen (800 mg in 500 ml saline) appeared less effective than IV dexketoprofen and IV metoclopramide (measured by a change in VAS at 30 min) in a small non‐placebo‐controlled prospective study 27 .…”
Section: Discussionmentioning
confidence: 99%
“…15 IV ibuprofen is as effective as IV ketorolac for treating perioperative pain. [16][17][18] IV ibuprofen may thus offer another parenteral NSAID option for acute headache treatment, but its efficacy in migraine is not well known. We hypothesized that IV ibuprofen reduces migraine pain intensity at 2 h after infusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation